2004
DOI: 10.1097/01.brs.0000131442.87202.39
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Ventral Epidural Pressure Response to Graded Spinal Canal Compromise and Spinal Motion

Abstract: CVEP is elevated by both spinal canal compromise and spinal motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Figure 3b shows the curve produced between the percentage of canal compromise (%) and the associated change in pressure. In comparison to Wolfla et al .,[8] who reported a sinusoidal increase in pressure, our measures fit a single-phase nonlinear model. This describes an immediate and rapid rise in pressure during the initial advancement of the DHS screw, with pressures showing incrementally smaller increases in pressure as the screw advanced.…”
Section: Resultssupporting
confidence: 46%
See 2 more Smart Citations
“…Figure 3b shows the curve produced between the percentage of canal compromise (%) and the associated change in pressure. In comparison to Wolfla et al .,[8] who reported a sinusoidal increase in pressure, our measures fit a single-phase nonlinear model. This describes an immediate and rapid rise in pressure during the initial advancement of the DHS screw, with pressures showing incrementally smaller increases in pressure as the screw advanced.…”
Section: Resultssupporting
confidence: 46%
“…quantified the effects of graded ventral spinal canal compromise in the cervical spine. [8] In the static condition, this study showed a sinusoidal association between epidural pressures and percent canal compromise, whereby the pressures remained minimal until canal compromised reached about 20%, after which they increased sharply until around 70% where they leveled off again. This suggests that the viscoelastic property of a spinal cord allows it to have some compensatory capacity to prevent acute injury.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Extradural compression induces a rapid increase of epidural pressure. Wolfla et al (2004) indicated that ventral cervical epidural pressure increases sharply when an epidural mass occupies more than 20% of the cervical vertebral canal space. According to our data, we calculated that our experimental model compromised more than 40% of the vertebral canal over C3 and C4 vertebral bodies.…”
Section: Digital Subtraction Venographymentioning
confidence: 99%
“…These results might be indirectly supported by previous clinical and experimental studies. Wolfla et al 44 reported that spinal cord compression was observed in a laminectomy model, and there was a residual dynamic compression in the flexed positions. Ito et al 2 also presented that flexion may be a not good posture for patients with myelopathy due to cervical OPLL.…”
Section: Discussionmentioning
confidence: 99%